2022
DOI: 10.1002/mnfr.202100959
|View full text |Cite
|
Sign up to set email alerts
|

Circulating (Poly)phenol Metabolites: Neuroprotection in a 3D Cell Model of Parkinson's Disease

Abstract: Scope: Diets rich in (poly)phenols have been associated with positive effects on neurodegenerative disorders, such as Parkinson's disease (PD). Several low-molecular weight (poly)phenol metabolites (LMWPM) are found in the plasma after consumption of (poly)phenol-rich food. It is expected that LMWPM, upon reaching the brain, may have beneficial effects against both oxidative stress and neuroinflammation, and possibly attenuate cell death mechanisms relate to the loss of dopaminergic neurons in PD. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 82 publications
2
10
0
Order By: Relevance
“…Knowing the three (poly)phenol metabolites transport kinetics across the endothelial cells of the BBB, and bearing in mind that at least one of them, Pyr-sulf, presented pleiotropic potential against oxidative stress, glutamate excitotoxicity, neuroinflammation and dopaminergic cell death[12, 22], we wondered what their contribution could be to improve barrier tightness. To this end, HBMEC were incubated with each of the metabolites at 5μM for 2h, and the expression of both β-catenin and ZO-1 were assessed by fluorescence microscopy ( Figure 2 ), key proteins for AJs and TJs, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowing the three (poly)phenol metabolites transport kinetics across the endothelial cells of the BBB, and bearing in mind that at least one of them, Pyr-sulf, presented pleiotropic potential against oxidative stress, glutamate excitotoxicity, neuroinflammation and dopaminergic cell death[12, 22], we wondered what their contribution could be to improve barrier tightness. To this end, HBMEC were incubated with each of the metabolites at 5μM for 2h, and the expression of both β-catenin and ZO-1 were assessed by fluorescence microscopy ( Figure 2 ), key proteins for AJs and TJs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in silico analysis suggested that none of these would be able to cross the BBB endothelium solely by passive permeation, thus active transport might be involved [12]. Remarkably, pre-treatment with these BBB permeable phenolic sulfates, in circulating concentrations, shown to improve cellular responses to excitotoxicity and oxidative and inflammatory injuries, particularly via modulation of NF-κB pathway [12] and two of them are strong attenuators of neurodegeneration against a dopaminergic insult in a three-dimensional neuronal model [22]. Such observations support our hypothesis that LMW (poly)phenol metabolites can be the true responsible for the reported brain health benefits arising from (poly)phenol reach diets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, polyphenols at dietary concentrations have been connected with the prevention and attenuation of PD through alternative mechanisms, including oxidative stress (i.e., a reduction of reactive oxygen species) and neuroinflammation reduction 211,212 .…”
Section: Small Molecule Drugsmentioning
confidence: 99%
“…An optimized highthroughput imaging approach was used and some phenyl-𝛾valerolactones and phenolic acids were able to inhibit spheroid aggregation. Spheroids were also used by Carecho et al [8] to demonstrate the neuroprotective effects of two phenolic metabolites that are able to cross the blood-brain barrier on a human 3D cell model of Parkinson's disease. This further supports the role of (poly)phenol metabolites in brain (patho)physiology.…”
mentioning
confidence: 99%
“…Spheroids were also used by Carecho et al. [ 8 ] to demonstrate the neuroprotective effects of two phenolic metabolites that are able to cross the blood‐brain barrier on a human 3D cell model of Parkinson's disease. This further supports the role of (poly)phenol metabolites in brain (patho)physiology.…”
mentioning
confidence: 99%